2006
DOI: 10.1002/ijc.22385
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of magnetic resonance imaging of dendritic cells for in vivo tracking of cellular cancer vaccines

Abstract: Success of immunotherapy with dendritic cells (DC) to treat cancer is highly dependent on their interaction with and activation of antigen specific T cells. To maximize DC-T cell contact accurate delivery of the therapeutic cells into the lymph node, or efficient trafficking of DC to the lymph nodes of the patient is essential. Since responses are seen in some patients but not in others, monitoring of the injected cells may be of major importance. Tracking of cells with magnetic resonance (MR) imaging is a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 39 publications
(97 reference statements)
0
76
2
Order By: Relevance
“…Cells containing iron were found to carry an average amount of 31.8 ± 0.7 µg per 1 × 10 6 cells in immature dendritic cells and 35.6 ± 1.0 µg per 1 × 10 6 cells in mature dendritic cells ( Figure 6). Verdijk et al 25 have shown that an average of 30 µg iron per 1 × 10 6 cells will not hinder cell viability, with the concentration of SPIO in their study set as 200 µg ferrum oxide/mL and a coculture time of 4 days. In contrast, this type of synthetic SPIO was shown to be more easily inserted, independent of concentration or coculture time, than suggested by previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells containing iron were found to carry an average amount of 31.8 ± 0.7 µg per 1 × 10 6 cells in immature dendritic cells and 35.6 ± 1.0 µg per 1 × 10 6 cells in mature dendritic cells ( Figure 6). Verdijk et al 25 have shown that an average of 30 µg iron per 1 × 10 6 cells will not hinder cell viability, with the concentration of SPIO in their study set as 200 µg ferrum oxide/mL and a coculture time of 4 days. In contrast, this type of synthetic SPIO was shown to be more easily inserted, independent of concentration or coculture time, than suggested by previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this type of synthetic SPIO was shown to be more easily inserted, independent of concentration or coculture time, than suggested by previous reports. 25,26 To confirm whether SPIO labeling could affect function and apoptosis of dendritic cells, the capacities of antigenprocessing, presenting, and naive allogeneic T cells stimulated by dendritic cells were tested by a mixed leukocyte reaction assay. The results showed that dendritic cells could maintain T cell activation and proliferation after being labeled by SPIO, except if the ratio of dendritic cells to T cells was 1:5, when the stimulating ability of mature dendritic cells was partly limited by SPIO.…”
Section: Discussionmentioning
confidence: 99%
“…11 Interestingly, our magnetic, GFP-expressing monocytes were able to reach poorly vascularized (that is, hypoxic) peri-necrotic areas of tumours which are notoriously difficult to target with viral or non-viral gene therapy vectors, indicating the potential therapeutic benefits of this technology. Previous studies have shown that various forms of cellular vector being developed for use in cell-based gene therapy protocols can be loaded with MNPs ex vivo including dendritic cells, 25 hematopoietic stem cell progenitors, 24 EC 26 and T cells. 27 To date, these MNP loaded cells have largely been used for imaging cells/tissues in vivo, but our data suggests that it might also be possible to use our magnetic targeting Magnetic cell-based gene therapy M Muthana et al approach to increase their targeting to diseased sites in cell-based gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…On day 5, DCs were loaded with a KLH and tumorassociated antigen peptides and labeled with SPIO by adding 100 mg Ferumoxide per ml (Endorem; Laboratoire Guerbet, Villepinte, France). 42 On day 7, DCs were matured with autologous monocyte-conditioned medium supplemented with prostaglandin-E2 (10 mg ml À1 ; Pharmacia & Upjohn, Erlangen, Germany) and 10 ng ml À1 recombinant tumor necrosis factor-a (Cellgenix) for 48 h as described previously. 43 At day 9, mature DCs were loaded with tumor-associated antigen peptides and subsequently labeled with 111 In-oxine (Covidien, Dublin, Ireland) in 0.1 mol l À1 Tris-HCl (pH 7.0) for 15 min at room temperature as described previously.…”
Section: Treatment Schedule and DC Preparation For Vaccinationmentioning
confidence: 99%